An inventory of human night-biting mosquitoes and their bionomics in Sumba, Indonesia. - Lepa Syahrani (PLoS Neglected Tropical Diseases, 2022)
Mosquitoes are important vectors that transmit pathogens to human and other vertebrates. Each mosquito species has specific ecological requirements and bionomic traits that impact human exposure to mosquito bites, and hence disease transmission and vector control. A study of human biting mosquitoes and their bionomic characteristics was conducted in West Sumba and Southwest Sumba Districts, Nusa Tenggara Timur Province, Indonesia from May 2015 to April 2018. Biweekly human landing catches (HLC) of night biting mosquitoes both indoors and outdoors caught a total of 73,507 mosquito specimens (59.7% non-Anopheles, 40.3% Anopheles). A minimum of 22 Culicinae species belonging to four genera (Aedes, Armigeres, Culex, Mansonia), and 13 Anophelinae species were identified. Culex quinquefasciatus was the dominant Culicinae species, Anopheles aconitus was the principal Anopheles species inland, while An. sundaicus was dominant closer to the coast. The overall human biting rate (HBR) was 10.548 bites per person per night (bpn) indoors and 10.551 bpn outdoors. Mosquitoes biting rates were slightly higher indoors for all genera with the exception of Anopheles, where biting rates were slightly higher outdoors. Diurnal and crepuscular Aedes and Armigeres demonstrated declining biting rates throughout the night while Culex and Anopheles biting rates peaked before midnight and then declined. Both anopheline and non-anopheline populations did not have a significant association with temperature (p = 0.3 and 0.88 respectively), or rainfall (p = 0.13 and 0.57 respectively). The point distribution of HBR and seasonal variables did not have a linear correlation. Data demonstrated similar mosquito-human interactions occurring outdoors and indoors and during early parts of the night implying both indoor and outdoor disease transmission potential in the area-pointing to the need for interventions in both spaces. Integrated vector analysis frameworks may enable better surveillance, monitoring and evaluation strategies for multiple diseases.